Gastric output of pancreatic secretory trypsin inhibitor is increased by misoprostol. Issue 11 (November 1991) - Playford, R J; Batten, J J; Freeman, T C; Beardshall, K; Vesey, D A; Fenn, G C; Baron, J H; Calam, J
Abstract : Pancreatic secretory trypsin inhibitor (PSTI) is a potent protease inhibitor that also has growth promoting activity. It has recently been identified in the foveolar cells of the stomach, which secrete mucus. We examined the effects of the prostaglandin E1 analogue misoprostol on gastric PSTI output. Seven normal volunteers took part. An initial period of gastric aspiration was followed by four 40 minute periods of gastric perfusion at 5 ml/minute of: 0.14 mol/l saline, 0.17 mmol/l bicarbonate, bicarbonate with misoprostol 400 micrograms, and then bicarbonate again. All perfusates contained polyethylene glycol 4000 as a marker. Misoprostol increased median gastric secretion of PSTI from 11 to 33 micrograms/hour (p less than 0.05), producing concentrations in gastric juice six times higher than those found in jejunal juice and about 1/30 of the values seen in pancreatic juice. Median mucus secretion increased to a lesser extent from 29 to 38 mg/hour during misoprostol. There was no change in intragastric concentrations of protein or of epidermal growth factor during infusion of misoprostol. Infusion of pentagastrin (6 micrograms/kg/hour) had no effect on gastric secretion of mucus, PSTI, or protein. Human gastric mucus was degraded on incubation with trypsin in vitro and this was prevented by the addition of PSTI. These results suggest that gastric PSTI may protect the gastric mucus layer against refluxed pancreatic proteases. Increased output of PSTI during microprostol may contribute to the protective effect of this drug.